Coacervates of whey proteins to protect and improve the oral delivery of a bioactive molecule. (November 2017) - Chapeau, Anne-Laure; Bertrand, Nicolas; Briard-Bion, Valérie; Hamon, Pascaline; Poncelet, Denis; Bouhallab, Saïd
Highlights: Heteroprotein coacervates ensure a high encapsulation efficiency of vitamin B9. Heterprotein coacervates protects B9 against physical degradation. Encapsulated vitamin showed improved bioavailability in rat. Abstract: The potentiality of heteroprotein complex coacervates as biocarrier for a bioactive was investigated. Vitamin B9 (B9), also known as folic acid, was encapsulated by complex coacervation of two whey proteins (WP), β-lactoglobulin and lactoferrin. The stability and bioavailability of formed B9-WP coacervates was then characterized. Under degradative conditions in vitro (UV light irradiation, and oxidation by H2 O2 ), WP coacervates protected the vitamin against chemical degradation. B9-WP coacervates also showed considerable physical stability over time when incorporated in real food matrices. Compared to unencapsulated B9, oral administration of B9-WP coacervates to healthy rats enhanced the plasma level of the vitamin. This improved bioavailability can be ascribed to the improvement in the solubility of B9 throughout the gastro-intestinal tract. We thus demonstrate the efficiency of WP coacervates as biocarrier for the protection and delivery of small bioactive molecules.